Burden and consequences of retained cardiovascular implantable electronic device lead fragments after heart transplantation. Issue 12 (24th April 2018) - Alvarez, Paulino A.; Sperry, Brett W.; Perez, Antonio L.; Varian, Kenneth; Raymond, Timothy; Tong, Michael; Hussein, Ayman A.; Taylor, David O.
Abstract : We performed a retrospective review of 402 consecutive patients who underwent heart transplantation at our institution between January 2009 and March 2017. A retained cardiovascular implantable electronic device (CIED) fragment was identified after transplantation in 49 of the 301 patients (16.2%) with CIED at baseline. Patients with retained fragments had leads with longer dwell times (median 2596 [1982, 3389] vs 1384 [610, 2202] days, P  < .001), higher prevalence of previously abandoned leads (14.3% vs 2.8%, P  = .003), and dual‐coil defibrillator leads (98% vs 81%, P  = .001) compared with patients without retained fragments. Five patients (10%) with retained CIED fragments underwent magnetic resonance imaging without adverse events. There was no difference in overall mortality between patients with and without CIED fragments (12% vs 11%, P  = .81) Patients with retained fragments located in the superior vena cava had significantly higher fluoroscopic times (3.3 vs 2.9 minutes, P  = .024) during subsequent endomyocardial biopsies. In a competing risk analysis, presence of a retained CIED fragment was associated with upper extremity deep venous thrombosis (sub hazard ratio [HR] 2.19, 95% confidence interval [CI] 1.17‐4.10, P  = .014) but not bloodstream infection after adjusting for potential confounders. In summary, retained CIED fragments are common after heart transplantation, and are associated with longer radiation exposure during biopsy procedures and upper extremity deep venous thrombosis. Abstract : Retained cardiovascular implantable electronic device lead fragments, which are present in 16% of patients after heart transplantation, are associated with longer radiation exposure during biopsy procedures and upper extremity deep vein thrombosis.